Development of stress model near the wellbore using an iterative coupling method - Bataee, M. (American Society of Civil Engineers (ASCE), 2017)
Water-alternating-gas (WAG) injection is increasingly applied globally as the effective enhanced oil recovery (EOR) method in oil wells. High injection pressure or low injection temperature could lead to wellbore failure. The rock stress around the wellbore is a function of the wellbore pressure and temperature, and it should be precisely determined to avoid wellbore failure. This study aimed to develop a wellbore geomechanical model for WAG injection using an iterative coupling method. The parameters of pressure, temperature, saturation, and stress were obtained for the multiphase flow condition using mathematical modeling. The finite-difference method was used to solve pressure, temperature, and saturation, and the finite-volume method was used to solve the rock stresses. Because the values for flow and rock stresses are related by the role of effective stress, the pressure is the key parameter to determine the stress. However, pressure changes with stress because of the change in porosity and permeability. Therefore, an iterative coupling method was employed to improve result accuracy. This paper introduces an improved iterative coupling method between flow and stress models that reduces the processing time of obtaining corrected stress results. © 2016 American Society of Civil Engineers.